THE CORRELATION BETWEEN STUDENTS’ HABIT IN LISTENING TO ENGLISH SONGS AND THEIR ENGLISH LISTENING COMPREHENSION SKILL - 'Afifah, Rasma (English Department of Faculty of Tarbiyah and Teacher Training, 2014)
This research describes the correlation between the students? habit in listening to English songs and their English listening comprehension skill of the seventh semester students in English Department of IAIN Antasari Academic Year 2012/2013. The problems that should be answered in this research are: (1) How is the students? habit in listening to English songs?, (2) How is the students English listening comprehension skill?, (3) Is there any correlation between their habit in listening to English songs and their English listening comprehension skill?. The subjects of the research are 72 of 79 students of seventh semester in English department of IAIN Antasari academic year 2012/2013. The object of this research is their habit in listening to English songs and their English listening comprehension skill, and correlation between them. The data are collected by some techniques, they are: written test, questionnaires, documentation, and interview. The result of the research indicates that the students? habit in listening to English songs is in Fair category and their English listening comprehension skill is in Very low category. The calculation of correlation result points out that the correlation between their habits in listening to English songs and their listening skill is very low so that the correlation is disregarded.